A rapid detection method for soil organic matter using a carbon dioxide sensor in situ. (28th February 2023) - Zhou, Tong; Jia, Cunhu; Zhang, Kailiang; Yang, Li; Zhang, Dongxing; Cui, Tao; He, Xiantao
Highlights: Dry combustion method can be used for rapid in-situ soil organic matter detection. Good fit of the linear model based on artificially proportioned soil samples. The prediction model is tested with natural soil and its accuracy is good. The method is easy to operate and is beneficial to the device integration. Abstract: Precision agriculture requires timely soil organic matter (SOM) detection in order to quickly obtain SOM information before sowing commences. Aiming to improve the slow detection speeds of traditional SOM detection methods, this study proposes a method using a CO2 sensor to measure CO2 produced by soil combustion at high temperatures. It then indirectly detects the SOM content by detecting the concentration of emitted CO2 . A prediction regression of SOM content is obtained using artificially proportioned soil, and the model is tested using four natural soil samples. The determination coefficient of the predicted SOM content by the model is 0.977, with the lowest achieved error rate of 5.65 %, the highest error rate of 18.29 %, and an average error rate of 12.61 %.